International Journal of E-Services and Mobile Applications - Budu, J.; Boateng, R. (IGI Publishing Hershey, PA, 2015)
Although there is vast literature about the contemporary mobile services m-services phenomenon, there is a lack of focus on the strategic processes through which m-services are developed. The dynamic capability framework which lends itself as an appropriate theoretical means of exploring this research gap also lack empirical testing within the m-service research space. The purpose of this paper is to begin to address these gaps in the literature by drawing how a Ghanaian m-services developer develops capabilities to create m-services. This case study gathered qualitative data through key informant interviews, participant observation and a review of accessible company documents, and e-mail correspondence. Drawing on literature on dynamic capabilities, this study draws three conclusions. First, there are four types of m-service capabilities that can be developed i.e. informational, interactional, transactional, and transformational m-service capabilities. Further, the type of m-service capability determines the type of m-service that can be provided. Second, political change determines the type of m-service capability that an m-service provider develops. Third, the extent to which an m-service impacts on its intended market is dependent on the extent of market readiness for that particular m-service type. This study's contribution lies in the operationalisation of the dynamic capability framework in the m-service context. This paper is the first to adapt the dynamic capability framework within the m-service setting to unearth an understanding of how m-service providers create capabilities to develop m-services.
Keywords: contemporary mobile services; m-services phenomenon; transformational m-service capabilities; e-mail correspondence; informational; interactional; transactional